Developing the M-H-IB Model to Explain the Mediational Role of Hedonism on Materialism and Impulse Buying Relationship : Proposing a Research Framework - Sen, Shaon (Indian Journal of Marketing, 2023)
Purpose : The present study aimed to bring together the stimulus factors, which includes materialism and hedonism, in describing impulse buying. The dynamic nature of the shift in consumers’ buying behavior prompts consumer researchers to respond to these changes, which becomes a key for marketers and practitioners to unlock the mist of need recognition among consumers and design effective marketing strategies accordingly. This study proposed a model where hedonism (H), which happens to be a precursor to impulse buying, is conceived as a mediator in the optimistic materialism (M) – impulse buying (IB) relationship. Methodology : This study is an extensive literature review of nationally and internationally published papers in peer-reviewed journals. The study incorporated all the relevant papers’ research findings that matched specific keyword search results. At the same time, this research paper undertook iterative search techniques to finalize the net-reviewed research papers. The study excluded articles that were not pertinent or did not fall under the abovementioned criteria. Findings : The extensive literature review prompted structuring of the hedonism-mediated optimistic materialism-impulse buying (M-H-IB) research framework. We found that this model is logically valid and seeks future empirical investigation. This finding provides a microscopic view of the understanding of impulse buying. Practical Implications : Studies in consumer behavior are essential because it helps consumer researchers understand the deep-rooted motivations that impose a change in consumers’ characteristics and psychology. Understanding these changes becomes a key for marketers and practitioners to unlock the mist of need recognition among consumers and design effective marketing communications and advertisements accordingly to market their offerings successfully. This study proposed a model where hedonism, which happens to be a precursor to impulse buying, is conceived as a mediator in the optimistic materialism–impulse buying relationship. Originality : Unlike prior research, this M-H-IB model is essential because it can establish a closed-loop estimation of the influence of materialism and hedonism on impulse buying. Further, this approach enriched consumer research by attempting to reduce the lack of defined marketing models in the research community.